Oral corticosteroid use, obesity, and ethnicity in children with asthma. (1st December 2020) - Lucas, Jennifer A.; Marino, Miguel; Fankhauser, Katie; Bailey, Steffani R.; Ezekiel-Herrera, David; Kaufmann, Jorge; Cowburn, Stuart; Suglia, Shakira F.; Bazemore, Andrew; Puro, Jon; Heintzman, John
Abstract: Objective : Comorbid asthma and obesity leads to poorer asthma outcomes, partially due to decreased response to controller medication. Increased oral steroid prescription, a marker of uncontrolled asthma, may follow. Little is known about this phenomenon among Latino children. Our objective was to determine whether obesity is associated with increased oral steroid prescription for children with asthma, and to assess potential disparities in these associations between Latino and non-Hispanic white children. Methods: We examined electronic health record data from the ADVANCE national network of community health centers. The sample included 16, 763 children aged 5–17 years with an asthma diagnosis and ≥1 ambulatory visit in ADVANCE clinics across 22 states between 2012 and 2017. Poisson regression analysis was used to examine the rate of oral steroid prescription overall and by ethnicity controlling for potential confounders. Results: Among Latino children, those who were always overweight/obese at study visits had a 15% higher rate of receiving an oral steroid prescription than those who were never overweight/obese [rate ratio (RR) = 1.15, 95% CI 1.05–1.26]. A similar effect size was observed for non-Hispanic white children, though the relationship was not statistically significant (RR = 1.10, 95% CI: 0.92–1.33). The interactions between body mass index and ethnicity were not significant (sometimes overweight/obese p = 0.95, always overweight/obese p = 0.58), suggesting a lack of disparities in the association between obesity and oral steroid prescription by ethnicity. Conclusions: Children with obesity received more oral steroid prescriptions than those at a healthy weight, which may be indicative of worse asthma control. We did not observe significant ethnic disparities.